The function-notation rule says to take whatever is the input, and plug it in for x in the formula. So:I'm unsure how I'd start on this. Initially I just added the given function with the values:
f(x)=(-6+x^2)(x+1)
f(x)+f(-7)(-6+x^2)
However, I'm pretty sure that I am doing something wrong.
View attachment 10455
The function-notation rule says to take whatever is the input, and plug it in for x in the formula. So:
. . . . .f(x) = 2x; f(3) = 6; f(0) = 0; f(@) = 2@
In your case, you need to plug "x + 1" in for every instance of x in the rule:
. . . . .f(x) = -6 + x^2
. . . . .f(x + 1) = -6 + [x + 1]^2 = -6 + x^2 + 2x + 1
...and so forth. Follow this standard methodology to get your final answers.![]()
''f(x + 1) = -6 + [x + 1]^2 = -6 + x^2 + 2x + 1'' That doesn't make complete sense to me. Why is it ''-6+[x+1]^2='' why is there an ^2 at the end ?
This makes me think that you're reading the notation f(x+1) as though it means f times (x+1).Given f(x)= -6+x^2, find … f(x+1)
… Initially I [did this]:
(-6+x^2)(x+1) …
This makes me think that you're reading the notation f(x+1) as though it means f times (x+1).
f(x+1) does not indicate multiplication. It's a special notation known as 'function notation'. Check your textbook's index or use Google, to learn about this notation. It is a very important notation to understand because it's used so much in math.
Let us know, if you see something in those lessons that you're still unsure about. :cool: